Suborder Endeostigmata Reuter, 1909. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Walter, David Evans; Bolton, Samuel; Uusitalo, Matti; Zhang, Zhi-Qiang (Zootaxa, 2011)
-